2020
DOI: 10.4102/ac.v20i1.853
|View full text |Cite
|
Sign up to set email alerts
|

Could conservation management be prioritised during captive wildlife experiences?

Abstract: Orientation: Wildlife rehabilitation centres and sanctuaries are experiencing increased pressure from conservationists and animal rights activists to eradicate captive wildlife interactions.Research purpose: Conservation management is a crucial aspect of these establishments. Research on how to enhance conservation management in these establishments, particularly in a South African context, is scant – a gap that this research fills.Research design, approach and method: This study was approached from the regula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…Section C measured 13 statements related to the extent to which respondents’ visits to the zoo may influence their PCI. The statements were based on Viljoen and Kruger (2020), Kruger and Viljoen (2021), Mellish et al (2019a), Mellish, Ryan, Pearson, and Tuckey (2019b) and Kelly and Skibins (2020). Section D captured motivational factors and measured 23 statements ranging from socialisation, escape, education and engagement.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Section C measured 13 statements related to the extent to which respondents’ visits to the zoo may influence their PCI. The statements were based on Viljoen and Kruger (2020), Kruger and Viljoen (2021), Mellish et al (2019a), Mellish, Ryan, Pearson, and Tuckey (2019b) and Kelly and Skibins (2020). Section D captured motivational factors and measured 23 statements ranging from socialisation, escape, education and engagement.…”
Section: Methodsmentioning
confidence: 99%
“…This implies that frequent and repeat zoo visitors show increased pro-conservation (PC) attitudes. In research focusing on captive wildlife experiences, Viljoen and Kruger (2020) found that the visitor motive "socialisation and participation" positively correlates with conservation management in these establishments. Accordingly, we suggest that specific visitor attributes (profile characteristics including demographics, socio-economics and motives) may influence PCI more than others, and therefore, we suggest the following hypotheses: H3(a 1 ).…”
Section: The Demand-side: Zoo Visitor Attributesmentioning
confidence: 99%
See 1 more Smart Citation